The interactions between traditional Chinese medicine and gut microbiota: Global research status and trends - Yang, Shanshan; Hao, Shaodong; Wang, Qin; Lou, Yanni; Jia, Liqun; Chen, Dongmei (Frontiers in Cellular and Infection Microbiology, 2022)
Background There is a crosstalk between traditional Chinese medicine (TCM) and gut microbiota (GM), many articles have studied and discussed the relationship between the two. The purpose of this study is to use bibliometric analysis to explore the research status and development trends of the TCM/GM research, identify and analyze the highly cited papers relating to the TCM/GM. Methods A literature search regarding TCM/GM publications from 2004 to 2021 was undertaken on August 13, 2022. The main information (full record and cited references) of publications was extracted from the Science Citation Index Expanded (SCI-E) of Web of Science Core Collection (WoSCC). The Bibliometrix of R package, CiteSpace and VOSviewer were used for bibliometric analysis. Results A total of 830 papers were included. The publication years of papers were from 2004 to 2021. The number of papers had increased rapidly since 2018. China had the most publications and made most contributions to this field. Nanjing University of Chinese Medicine and Beijing University of Chinese Medicine were in the leading productive position in TCM/GM research, Chinese Academy of Chinese Medical Sciences had the highest total citations (TC). Duan Jin-ao from Nanjing University of Chinese Medicine had the largest number of publications, and Tong Xiao-lin from China Academy of Chinese Medical Sciences had the most TC. The Journal of Ethnopharmacology had the most published papers and the most TC. The main themes in TCM/GM included the role of GM in TCM treatment of glucolipid metabolism diseases and lower gastrointestinal diseases; the mechanism of interactions between GM and TCM to treat diseases; the links between TCM/GM and metabolism; and the relationship between GM and oral bioavailability of TCM. Conclusion This study gained insight into the research status, hotspots and trends of global TCM/GM research, identified the most cited articles in TCM/GM and analyzed their characteristics, which may inform clinical researchers and practitioners’ future directions.